"Understanding my story": young person involvement in formulation. Issue 4 (2nd November 2020) - McKeown, Annette; Martin, Aisling; Kennedy, Patrick J.; Wilson, Amy
Abstract : Purpose: The SECURE STAIRS framework has promoted young person involvement as a key feature of innovative service provision. In the North East of England, Secure Children's Homes (SCHs) have pioneered young person involvement in team formulation. Young people have also led on the development of formulation materials through a young person involvement project. Young people's attendance at team formulation meetings has become embedded. These service developments have also begun to expand across broader SCHs, Secure Training Centres (STCs) and Young Offender Institutions (YOIs) and reflect the national impact of such pioneering developments. There is a notable lack of research examining the impact of young person involvement in formulation. The purpose of this study is to elucidate this area. Design/methodology/approach: Between April and August 2019, there were 86 staff attendances at formulation meetings where young people were present across two SCHs in the North East of England. Findings: Paired samples t -tests indicated staff-reported significant post-formulation improvements across all domains measured including knowledge [ t (85) = 11.38, p < 0.001]; confidence working with the young person [ t (85) = 5.87, p < 0.001]; motivation [ t (85) = 3.58, p < 0.001]; understanding [ t (85) = 9.03, p < 0.001]; and satisfaction with the treatment plan [ t (85) = 8.63, p < 0.001]. Research limitations/implications: Implications of findings are discussed and further developments outlined. Practical implications: Young people attending team formulation is a new and evolving area, and to the best of the authors' knowledge, there is no existing research evaluating this area. The current findings suggest that staff knowledge, motivation, confidence and satisfaction with the treatment plan is improved following attendance at team formulation where the young person is present and actively participating. Young people's participation and involvement is central to planning, developing and progressing meaningful provision within children and young people secure provision. Social implications: Involving children and young people in decision-making, service development and evaluation are also key components of ensuring the voice of young people is central in our minds. It also supports empowering the young people we work with. Young people and their journey should always be at the heart of what we do. Originality/value: Young people attending team formulation is a new and evolving area, and to the best of the authors' knowledge, there is no existing research evaluating this area. This is the first study of its type evaluating formulation directions within the SECURE STAIRS framework.